PENINGKATAN HASIL BELAJAR PERKALIAN DENGAN TEKNIK BERSUSUN KE BAWAH MENGGUNAKAN ALAT PERAGA TABEL PERKALIAN PINTAR KELAS III SD NEGERI 20 KECAMATAN PONTIANAK SELATAN - Judyanto Sirait; Ria Novita Rini; Pariyah; Salma Salsabila; Suriyani; Uyun Maskuro; Wilda Zakia; Yoseph Maunino (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low mathematics learning outcomes of third-grade students at SD Negeri 20 Kecamatan Pontianak Selatan on multiplication operations. Preliminary evaluation results showed that only 9 out of 25 students (36%) achieved the minimum learning mastery criteria, while 16 students (64%) had not yet achieved mastery. This condition was caused by teacher-centered learning, limited use of concrete and engaging instructional media, and low student participation in the learning process. Therefore, this study aimed to improve students’ mathematics learning outcomes through the use of Takalintar media. This study employed Classroom Action Research (CAR) conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection stages. The participants were 25 third-grade students of SD Negeri 20 Kecamatan Pontianak Selatan in the 2025/2026 academic year. Data were collected through tests, observations, and documentation and analyzed using quantitative and qualitative techniques. The results showed a significant improvement in students’ learning outcomes. The average score increased from 58.40 in the pre-cycle stage with a classical mastery level of 36%, to 64.80 in Cycle I with a mastery level of 52%, and further to 83.20 in Cycle II with a mastery level of 88%. Observation results also indicated increased teacher and student activity during the learning process. These findings suggest that the use of Takalintar media is effective in improving mathematics learning outcomes on multiplication operations among third-grade students at SD Negeri 20 Kecamatan Pontianak Selatan